2011
DOI: 10.1158/0008-5472.can-10-4635
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 and -2 Exert Antagonistic Functions in Tumor Angiogenesis, yet Both Induce Lymphangiogenesis

Abstract: Members of the Angiopoietin family regulate various aspects of physiologic and pathologic angiogenesis. Although Angiopoietin-1 (Ang-1) decreases endothelial cell permeability and increases vascular stabilization via recruitment of pericytes and smooth muscle cells to growing blood vessels, Angiopoietin-2 (Ang-2) mediates angiogenic sprouting and vascular regression. In this study, we used the Rip1Tag2 transgenic mouse model of pancreatic b-cell carcinogenesis to investigate the roles of Ang-1 and Ang-2 in tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 45 publications
4
65
0
1
Order By: Relevance
“…TGFβ inhibits EC proliferation and stimulates mural cell differentiation into SMCs or perivascular cells, as well as affecting matrix deposition (Heimark et al, 1986;D'Amore and Smith, 1993). ANG1, which activates ligands for TIE2 (endothelial-specific receptor tyrosine kinase; TEK), is expressed by mural cells and stimulates mural coverage and basement membrane deposition, thereby promoting vessel tightness, whereas angiopoietin 2 (ANG2 or ANGPT2), which is an antagonist to ANG1 and TIE2 signaling, promotes mural cell detachment and EC sprouting, resulting in angiogenesis (Fagiani et al, 2011;Yu et al, 2013). Accumulating evidence demonstrates that stromal cell-derived factor 1 (SDF1) and insulin-like GF (IGF) stimulate angiogenesis through recruitment of EPCs from bone marrow and enhanced EPC mobilization (Maeng et al, 2009;Jujo et al, 2010).…”
Section: Growth Factors Are Crucial During Vascular Formationmentioning
confidence: 99%
“…TGFβ inhibits EC proliferation and stimulates mural cell differentiation into SMCs or perivascular cells, as well as affecting matrix deposition (Heimark et al, 1986;D'Amore and Smith, 1993). ANG1, which activates ligands for TIE2 (endothelial-specific receptor tyrosine kinase; TEK), is expressed by mural cells and stimulates mural coverage and basement membrane deposition, thereby promoting vessel tightness, whereas angiopoietin 2 (ANG2 or ANGPT2), which is an antagonist to ANG1 and TIE2 signaling, promotes mural cell detachment and EC sprouting, resulting in angiogenesis (Fagiani et al, 2011;Yu et al, 2013). Accumulating evidence demonstrates that stromal cell-derived factor 1 (SDF1) and insulin-like GF (IGF) stimulate angiogenesis through recruitment of EPCs from bone marrow and enhanced EPC mobilization (Maeng et al, 2009;Jujo et al, 2010).…”
Section: Growth Factors Are Crucial During Vascular Formationmentioning
confidence: 99%
“…Consistently, recombinant ANGPT1 protein and adenoviral vector-mediated overexpression of ANGPT1 were shown to induce lymphatic vessel sprouting and hyperplasia (Morisada et al 2005;Tammela et al 2005). The lymphangiogenic effect of ANGPT1 was also shown in a transgenic mouse model, where overexpression of ANGPT1 or ANGPT2 in pancreatic β-cells was shown to induce peri-insular lymphangiogenesis (Fagiani et al 2011). Both ANGPT1 and ANGPT2 bind to TIE-2, and TIE-2-mediated signaling is crucial for blood vascular maturation and the maintenance of its integrity (Augustin et al 2009).…”
Section: Targeting Lecs To Suppress Tumor Metastasismentioning
confidence: 70%
“…While Ang-1 can activate Tie-2, Ang-2 has a similar affinity for Tie-2, but does not activate it, and competes with Ang-1 for Tie-2 binding. It has been shown that Ang-1 is an agonist for endothelial cells and that Ang-2 can act as a context-dependent antagonist (21). Studies demonstrated that Ang-1 is essential for vascular development by promoting blood vessel maturation (9), and by inhibiting vessel leakage, endothelial apoptosis, and microvascular regression (22).…”
Section: Discussionmentioning
confidence: 99%